STAGES OF TECHNICAL TRAINING OF ATHLETES - Khudayberdieva Dilafruz Abidovna; Abbasov Bakhadir Asatillaevich (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The pedagogical process is aimed at studying the details of the motor action. Particular attention is paid to methods based on the use of motor perception. At this stage, a rational kinematic and dynamic structure of movements is formed. In order to form an expedient rhythm of motor actions, a wide range of traditional methods and means are used, aimed at creating an integral picture of a motor action, combining its parts into a single whole. This article tells exactly how to organize the actions of athletes during technical training.